2010
DOI: 10.1097/rlu.0b013e3181e9fa7a
|View full text |Cite
|
Sign up to set email alerts
|

Brain Single Photon Emission Computed Tomography With Tc-99m MIBI or Tc-99m ECD in Comparison to MRI in Multiple Sclerosis

Abstract: Purpose: To evaluate whether or not brain single photon emission computed tomography (SPECT) with Tc-99m MIBI or Tc-99m ECD (ethyl cysteinate dimer) can detect any abnormality in patients with definite multiple sclerosis (MS). We then compared these values with the results of T1, T2, and fluid-attenuated inversion recovery in magnetic resonance imaging (MRI). Materials and Methods: A total of 16 patients with proved MS were enrolled in the study, and the MRI with and without gadolinium contrast and also brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…Luke et al, who used single photon emission computed tomography (SPECT), showed hypoperfusion of cerebral blood flow (CBF) in the gray matter (GM) of the frontal lobe of patients with progressive MS compared with cerebral perfusion in control patients, although the study reported normal perfusion in patients with RR-MS [ 6 ]. Our previous study has similar results and normal brain perfusion of MS patients in the early stage and without significant disability [ 7 ]. In another study, Brooks et al showed that there was decreasing CBF and oxygen utilization in both the white matter and the cortical GM in the MS patients compared to the healthy control group [ 8 ].…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Luke et al, who used single photon emission computed tomography (SPECT), showed hypoperfusion of cerebral blood flow (CBF) in the gray matter (GM) of the frontal lobe of patients with progressive MS compared with cerebral perfusion in control patients, although the study reported normal perfusion in patients with RR-MS [ 6 ]. Our previous study has similar results and normal brain perfusion of MS patients in the early stage and without significant disability [ 7 ]. In another study, Brooks et al showed that there was decreasing CBF and oxygen utilization in both the white matter and the cortical GM in the MS patients compared to the healthy control group [ 8 ].…”
Section: Introductionsupporting
confidence: 64%
“…Perfusion studies of MS have different results that may be due to various perfusion measurement techniques and stages of disease [ 6 , 7 ]. In our previous study, we investigated cerebral perfusion in early RR-MS patients with mild or no disability, which determined normal cerebral perfusion in all patients [ 7 ]. Other studies showed different brain perfusion in MS patients particularly in those with a progressive type of disease [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is an inflammatory disease of the central nervous system (CNS) that involves myelin, oligodendrocytes and axons and culminates in consecutive neuronal death and progressive neurologic disability [1,2]. Histopathological work-ups have demonstrated apoptotic neuronal cell death in demyelinated cerebral cortex lesions of MS patients [3] that cannot be identified by magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Assadi et al (2010), evaluated the efficacy of SPECT imaging with Tc-99m MIBI or Tc-99m ECD to detect abnormal perfusion in MS patients and compared these values with results obtained on MRI (T1, T2, and fluid-attenuated inversion recovery) with and without the use of gadolinium contrast. The authors report that MRI was able to detect an average of 10.47, 3.7, 5.3, 1.7, and 0.9 lesions in the periventricular white matter, juxtacortical white matter, corpus callosum, cerebellar peduncles and brainstem.…”
Section: Single-photon Emission Computed Tomography (Spect) Correlates Of Cognitive Impairment In Msmentioning
confidence: 99%